2018
DOI: 10.1177/0260106018777336
|View full text |Cite
|
Sign up to set email alerts
|

Can bone-regulating hormones and nutrients help characterize the metabolically healthy obese phenotype

Abstract: These findings suggest that bone-regulating hormones and nutrients, especially serum PTH, osteocalcin concentrations, and dietary Mg intakes, can help to characterize the MHO phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
1
3
3
1
Order By: Relevance
“…Therefore, they concluded that diet composition does not explain the absence of cardiometabolic abnormalities in obese adults. However, Sukumar et al 19 stated that dietary magnesium intake might help to characterize the MHO phenotype, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, they concluded that diet composition does not explain the absence of cardiometabolic abnormalities in obese adults. However, Sukumar et al 19 stated that dietary magnesium intake might help to characterize the MHO phenotype, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Inconsistencies between the study by Hankinson et al 18 and the results from Sukumar et al 19 and our study could be related to the definition of the MHO phenotype.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, our findings may be explained through the bone-regulating role of hormones and nutrients. A novel study showed that MHO adults had higher serum concentrations of ionized magnesium, dietary magnesium intakes, and serum osteocalcin while lower serum PTH compared to MUO adults (38). Magnesium, together with the thyroid and parathyroid glands support bone health by stimulating the production of calcitonin, known to act as a bonepreserving hormone and regulating PTH (39).…”
Section: Discussionmentioning
confidence: 99%
“…Teniendo en cuenta los niveles séricos de Mg encontrados en nuestro estudio, el 96% de los hombres los tenían dentro del rango normal, lo que dificulta cualquier interpretación de nuestros hallazgos. Las interrelaciones complejas no se pueden interpretar directamente, sin embargo, una investigación reciente presentó, como un intento, lo que llamaron sujetos "obesos metabólicamente saludables/no saludables", que incluían PTH sérica, Mg, VD y otros parámetros, para hacer la distinción (36) .…”
Section: Discussionunclassified